Assuming usual notation, I derive the floating rate and fixed rate payoffs and set them equal. The par swap rate I get thus is:

$$S_{mn}\mid_{t=0} = {\sum_{i=m}^{N-1} \tau_i L(0, T_{i-1}, T_i)Z_{0i} \over \sum_{n=m}^{N-1} \tau \cdot Z_{0i}}$$

When the $L$ and $Z$ curves are identical, the following can result as per the textbook - but I am not sure how?

$$S_{mn} = {Z_{0m} - Z_{0n} \over \sum_{i=0}^{N-1} \tau \cdot Z_{0i}}$$


If $L$ and $Z$ curves are identical, you are in a single curve frame work.

A swap can be seen as a long position in a fixed rate bond and a short position in a floating rate bond. (I'll use yearly payments 30/360 in order to be able to ignore the $\tau$ =1 and simplify the notation)

$$DF_1 \times C^{fixed} + ... + DF_n \times C^{fixed} + DF_n - (DF_1 \times C_1^{float} + ... + DF_n \times C_n^{float} + DF_n ) = 0$$

But because in a single curve framework (forward curve = discount curve) a floating rate bond with zero spread will always be at par, you have:

$$DF_1 \times C_1^{float} + ... + DF_n \times C_n^{float} + DF_n = 1$$

and so you only have to worry about the fixed leg:

$$DF_1 \times C^{fixed} + ... + DF_n \times C^{fixed} + DF_n - 1 = 0 $$

$$DF_1 \times C^{fixed} + ... + DF_n \times C^{fixed} + DF_n = 1 $$

If you rearrange this in terms of the fixed rate ($C^{fixed}$), you get:

$$C^{fixed} = \frac{1 - DF_n}{\sum^n_{i=1}DF_i}$$

Which is the formula you showed, just with a different notation.

The intuition of this formula is that you are determining the fixed rate on a bond where the sum of the present value of the interest payments plus the price of the zero coupon bond will be one.

You can also easily adjust this for a forward starting swap.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.